Dari Ruang Ritual ke Ruang Sosial: Masjid sebagai Institusi Sosial Keagamaan dalam Perspektif Sosiologi Agama - Basri, Faisal (Jurnal JINNSA (Jurnal Interdipliner Sosiologi Agama), 2025)
The mosque is a central religious institution in Muslim societies. However, its role is often narrowly understood as merely a place for ritual worship. This article aims to analyze the functions of the mosque from the perspective of the sociology of religion by conceptualizing it as a socio-religious institution with multidimensional roles in society. This study employs a qualitative approach through library research. Data were collected from classical and contemporary works in the sociology of religion, Islamic studies, and relevant scholarly articles, and analyzed using content analysis techniques. The theoretical framework draws on Émile Durkheim’s theory of social solidarity, Max Weber’s theory of social action, and Peter L. Berger’s theory of the social construction of reality. The findings indicate that the mosque performs several key functions: a ritual function that strengthens social solidarity and collective consciousness; a social function as a religious public space and a center of community integration; an educational function in transmitting and reproducing religious values; an economic function through the management of zakat, infaq, and almsgiving; and a cultural function as a symbol of identity and a site for negotiating religious values and local culture. This article argues that the mosque is a dynamic socio-religious actor with significant potential to contribute to the development of a religious, inclusive, and socially cohesive society. Strengthening the social functions of mosques is therefore essential to ensure their relevance in responding to contemporary social dynamics.